The Role of Business Credit on SME Performance, Regional Economic Output, and Unemployment - Husnah Husnah; Suparman Suparman; Rustam Abdul Rauf (Research Horizon, 2023)
This study aims to determine the effect of people's business credit on the development of small and medium enterprises, increased output, and unemploymsent in Central Sulawesi by analyzing it from a micro and macro perspective. The micro aspect will analyze the effect of People's Business Credit (KUR) on Small and Medium-Sized Enterprises (SMEs) business actors who will utilize primary data with the scope of the research area including: Palu City; Banggai Regency; Poso Regency; Toli-Toli District; and Poso District. Meanwhile, the macro aspect will utilize the Simultaneous Equation method to see the effect of increasing capital (KUR) on output and employment. The results show that people's business credit has a significant and positive effect on the business profits of the recipient of the credit. In addition, there was an increase in labor after receiving credit by 1%. The suggestion put forward is that the addition of working capital from KUR continues to be increased, this is because the addition of labor is proven to increase sales turnover and business profits.